The Effect of Public Ownership on Timeliness of Financial Reporting - Sagung Oka Pradnyawati; Kadek Indah Kusuma Dewi; Ida Ayu Rayhita Santhi (AIBPM Publisher, 2022)
The timeliness of financial statement publication is important because it becomes the qualitative characteristics of useful information in supporting the relevance of the information. Besides how quickly a company publishes its financial statements will tend to affect the trust of financial statement users. This research aims to find the effect of public ownership on the timeliness of financial reporting. Total samples are 39 of property and real estate companies listed on the Indonesia Stock Exchange (IDX) in a period of 2018-2020 and analyzed by Statistical Package for the Social Sciences (SPSS). This research finds that public ownership has no effect on the timeliness of financial reporting. The value of public ownership is low so that the public is not able to affect company policy, especially in the quality of a financial statements.Â Keywords: timeliness, public ownership, financial statements.